MENTAL HEALTH CHALLENGES AMONG UNIVERSITY STUDENTS IN THE DIGITAL ERA - Anarbekova Gulzodabegim,; G’ulomjonov Shohjahon,; Ramazonov Khumoyiddin, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The growth of digital technology has had a significant impact on both university education and daily student life. Digital platforms make communication easier and give students instant access to course materials, but they also bring up new psychological strains. This study explores the behavior-related and mental issues that learners in higher education encounter in the digital age. Survey research and semi-structured interviews are used in this study to find trends in academic overload, stress, anxiety, and excessive internet engagement. The results show that mental strain is increased by extended screen time, constant online availability, and social network comparison. In a world that is becoming more connected the overview points out practical steps that both learners and educational institutions can take to boost their mental resilience.